2019
DOI: 10.3390/ma12172751
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Plasma-Liquid Systems: A Review

Abstract: Plasma-liquid systems have attracted increasing attention in recent years, owing to their high potential in material processing and nanoscience, environmental remediation, sterilization, biomedicine, and food applications. Due to the multidisciplinary character of this scientific field and due to its broad range of established and promising applications, an updated overview is required, addressing the various applications of plasma-liquid systems till now. In the present review, after a brief historical introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 328 publications
0
92
0
1
Order By: Relevance
“…Plasma-liquid interaction has attracted increasing attention in recent years. e ability of plasma technology in plasmaliquid interaction, which has been confirmed due to the results of previous studies, along with the critical issue of water pollution as well as the lack of potable water, has led to the emergence of wide studies pointing to the use of different types of discharge plasma for water purification and wastewater treatment to improve their quality [1]. Nonthermal plasma is a type of plasma in which the electron temperature is much more than the ion temperature, but the overall plasma temperature remains low.…”
Section: Introductionmentioning
confidence: 85%
“…Plasma-liquid interaction has attracted increasing attention in recent years. e ability of plasma technology in plasmaliquid interaction, which has been confirmed due to the results of previous studies, along with the critical issue of water pollution as well as the lack of potable water, has led to the emergence of wide studies pointing to the use of different types of discharge plasma for water purification and wastewater treatment to improve their quality [1]. Nonthermal plasma is a type of plasma in which the electron temperature is much more than the ion temperature, but the overall plasma temperature remains low.…”
Section: Introductionmentioning
confidence: 85%
“…Electrode geometric construction and phase patterns of liquid-phase plasmas can be categorized into four groups: (1) direct electrical discharge between two electrodes [23], (2) contact electrical discharge between electrodes and the surface of the surrounding electrolyte, (3) miscible electrical discharge with external gas injection, and (4) special excitation electrical discharge (i.e., radio frequency, microwave irradiation or laser ablation). In this section, we will discuss on the direct discharge between two electrodes under the liquid-phase, which are presented by various terms.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%
“…These ions create vortex motions in water and other surface constituents with dipole properties, when subjected to an external electric field (Relvas et al 2015). In the literature, several studies can be found on enhanced water evaporation or drying from various materials when exposed to DBD (Hijosa-Valsero et al 2013;Iervolino et al 2019;Molina et al 2014) and other plasma discharges (Buβler et al 2017;Foster 2017;Gamaleev et al 2019;Morshed et al 2012;Rezaei et al 2019;Wang et al 2012;Zhang et al 2019).…”
Section: Wood Mass Loss During Ptmentioning
confidence: 99%